RESPIRATORY FUNCTIONS IN TEXTILE MILL WORKERS: ROLE OF PEAK EXPIRATORY FLOW RATE - Gupta, Seema; Malhotra, Varun; Tripathi, Yogesh; Dev, Pratibha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background: Textile industries play a significant role in economical growth of the country. Health concern of these textile mill workers is the biggest challenge. Respiratory alterations were found in these workers with long term exposure of cotton dust. Effect of cotton dust on peak expiratory flow rate is not very well documented in the past. Aim/objective: The main objective of this study was the assessment of respiratory functions in textile mill workers along with the effect on peak expiratory flow rate in these workers. Material & Methods: 130 male textile mill workers were recruited for this study from the different sections of a textile mill. In which, 80 workers were present from exposed and remaining 50 were from non exposed area of a textile mill. 30 to 40 year of age workers with the working history of not more than 5 years, were included for the part of the study. Their Body mass index and respiratory functions were evaluated. Body mass index was calculated by using weight and height of an individual. Respiratory functions including Forced vital capacity and forced expiratory volume in 1 second was estimated by using spirometer and peak expiratory flow rate was measured by means of Wright's peak flow meter. Results: the mean values of FVC, FEV1 and PEFR were found to be significantly (<0.01) lower in exposed group of textile mill when compared non exposed groups. When these values were compared on the basis of BMI, workers with BMI>25kg/m2 were found with lower mean values of FVC, FEV1 and PEFR when compared with workers with BMI<25kg/m2. Also there was significant (<0.05) negative correlation between BMI and PEFR in both exposed group and non exposed group of a textile mill. Conclusion: Workers in textile mill, with short term exposure of cotton dust may also present with respiratory alterations which may increase with long term exposure. Safety controls such as ventilation, etc and routine health check are very much required in textile industries. Keywords: Peak expiratory flow rate, Body mass index, Textile mill. Â  Â 